A survey of individuals’ willingness to share real-world data postmortem with researchers - Hendricks-Sturrup, Rachele M.; Lu, Christine Y. (Journal of clinical and translational science, 2024)
Objective:As posthumous data use policy within the broader scope of navigating postmortem data privacy is a procedurally complex landscape, our study addresses this by exploring patterns in individuals’ willingness to donate data with health researchers after death and developing practical recommendations.Methods:An electronic survey was conducted in April 2021 among adults (≥18 years of age) registered in ResearchMatch (www.researchmatch.org), a national health research registry. Descriptive statistics were used to observe trends in, and multinomial logistic regression analyses were conducted at a 95% confidence interval to determine the association between, willingness to donate some, all, or no data after death with researchers based on the participants’ demographics (education level, age range, duration of using online medical websites, and annual frequency of getting ill).Results:Of 399 responses, most participants were willing to donate health data (electronic medical record data [67%], prescription history data [63%], genetic data [54%], and fitness tracker data [53%]) after death. Among 397 respondents, we identified that individuals were more likely to donate some data after death (vs. no data) if they had longer duration of using online medical websites (adjusted relative risk ratio = 1.22, p= 0.04, 95% CI: 1.01 to 1.48). No additional significant findings were observed between willingness to donate all, some, or none of their data after death and other demographic factors.Conclusions:Engaging patients in online medical websites may be one potential mechanism to encourage or inspire individuals to participate in posthumous data donation for health research purposes.